Regular maintenance training for electronic fuel injection systems at Vocational High School 1 Lembah Melintang - Milana, Milana; Hidayat, Nuzul; Setiawan, Muhammad Yasep; Purwanto, Wawan; Arif, Ahmad (Universitas Muhammadiyah Magelang, 2022)
Numerous obstacles must be overcome by vocational schools, particularly in the area of developing technical and practical knowledge. The provision of skills improvement and reskilling for teachers and students, especially in the field of Electronic Fuel Injection (EFI) in gasoline-powered vehicles, is the most fundamental issue at SMKN 1 Lembah Melintang that needs special attention, particularly for Automotive Light Vehicle Engineering (TKRO). The program's goal is to increase teachers' and students' proficiency in the use of tools and procedures for regular maintenance of the EFI system in cars. With a portion of 30:70, the participants will receive both theoretical and practical training. The results of the pretest and posttest show that this program has increased the competence and expertise of teachers and students. This is proved by significant growth from the prior competency in the use of tools and circular work steps, with student gains of 24% and teacher gains of 14%.